Molecular docking, synthesis and biological evaluation of Vascular Endothelial Growth Factor (VEGF) B based peptide as antiangiogenic agent targeting the second domain of the Vascular Endothelial Growth Factor Receptor 1 (VEGFR1D2) for anticancer application - Afsaneh Sadremomtaz (11210280) (2020)
Tumor angiogenesis is regulated by the binding of VEGF to receptors (VEGFRs). The major mediator of tumor angiogenesis is VEGFA, more commonly referred to as VEGF. VEGFR1 binds VEGF with higher affinity (10 times) than VEGFR2.1 However, the role of the VEGFR1 in VEGF-mediated angiogenesis remains a mystery. Other Information Published in: Signal Transduction and Targeted Therapy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41392-020-0177-z